ANGPTL2 activity in cardiac pathologies accelerates heart failure by perturbing cardiac function and energy metabolism - Zhe Tian (Nature Portfolio, 2016)
Heart responds to increased workload by enlarging cardiomyocytes to preserve function, but in pathologies hypertrophy leads to heart failure. Here the authors show that ANGPTL2 activity in the heart is critical for determining beneficial vs. pathological hypertrophy via its effect on AKT-SERCA2a signaling and myocardial energy.